Intermarium – a vision, an illusion, or ... a reason of state? From the history of Polish political thought and practice - Waingertner, Andrzej (2022)
Attempts to build political and military security and favorable conditions for the economic development of Poland by constructing a broader political order in Central and Eastern Europe date back to the late Middle Ages. The Piasts built the security of their domain through victorious wars, expansion of borders and treaties with neighbours. The decline of this dynasty's reign was marked by an attempt to build a Polish-Hungarian personal union. In 1385, the idea of a Polish-Lithuanian personal union was realized. In 1569 it was replaced by the real union and the construction of the Polish-Lithuanian Commonwealth. After the partitions, interwar Poland tried to implement the idea of a federation of Poland with Ukraine, Belarus and Lithuania; the union of states between the Baltic Sea, the Black Sea and the Adriatic Sea; finally, the so-called Third Europe. During the years of World War II and the post-war division of the Old Continent, Polish political emigration did not abandon the integration concepts for Central and Eastern Europe. The bankruptcy of communism and the collapse of the USSR and the Eastern Bloc favored the restitution of the subjectivity of Poland and Eastern European countries and the region adopting a common, successful course for joining NATO and the EU. In 1991, the Visegrad Group was established. Since 2015, Poland has been implementing the Three Seas Initiative (ABC) project. It was based on a real community of economic, political and defense interests in the region. Intermarium is a permanent, ambitious, geopolitical vision. It was also an illusion, negatively verified by history. Above all, however, it is a concept resulting from Poland leading to the strengthening of its security, subjectivity and economic potential in the international area.
Keywords: History of Poland in the 20th century; History of Central and Eastern Europe in the 20th century; Polish political thought in the 20th century; Polish foreign policy in the 20th century